Cereal bars made from brewers’ spent grain, apple and Spirulina platensis: antioxidant activity and antihyperglycaemic effects (Research, Society and Development, 2021)
Increase in diabetes prevalence has led to the need to develop practical food that has fewer available carbohydrates and/or nutrients with positive effects on postprandial glycaemia. This study aimed at evaluating the feasibility of using brewers’ spent grain (BSG) at different ratios and granulometry (1.44 and 1.09 mm), along with Spirulina platensis biomass and dehydrated apples (DA), to produce cereal bars. Acceptability of formulations that had the highest percentages of DA was about 70%. Not only in vitro antioxidant activity, but also in vivo glycaemic response, glycaemic index (GI) and glycaemic load (GL) of cereal bars made from BSG and DA and of the ones with S. platensis were evaluated and compared to commercial cereal bars (CB). Cereal bars with S. platensis exhibited the highest content of phenolic compounds (124.28± 10.67 mg GAE/ 100 g), besides 22.47± 0.39 g/100 g of dietary fibre, which helped to decrease glycaemic response.